A magyar revízió és Burgenland kérdése - Gulyás, László (Közép-Európai Közlemények, 2015)
The Trianon peace treaty annexed a thin strip of land of Western-Hungary (4000 km2 with 292 000 inhabitants) to Austria. This territory became the ninth province of the Austrian state under the name Burgenland. After the referendum in Sopron (December 14-16, 1921), the Burgenland issue was no longer among topics that defined Austrian-Hungarian relations. According to our knowledge, there were two cases between 1921 and 1938 when the issue of Burgenland posed a problem for the leaders of Hungarian foreign affairs. One occasion was when it emerged as a subtheme in Lord Rothemere’s revision campaign for Hungary in 1927 and the question brought about some diplomatic complications. This is presented in the first section of the paper. The second time was after the fall of the Austrian state (Anschluss) in March 1938, when Burgenland caused a significant tension in Hungarian-German relations. The second part of our paper presents this issue.